Structural requirement of chalcones for the inhibitory activity of interleukin-5 - Yang, Hyun-Mo; Shin, Hye-Rim; Cho, Soo-Hyun; Bang, Seong-Cheol; Song, Gyu-Yong; Ju, Jung-Hun; Kim, Mi-Kyeong; Lee, Seung-Ho; Ryu, Jae-Chun; Kim, Youngsoo; Jung, Sang-Hun (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
Novel chalcones were found as potent inhibitors of interleukin (IL)-5. 1-(2-Benzyloxy-6-hydroxyphenyl)-3-(4-hydroxyphenyl)-2-propen-1-one (2b, 78.8% inhibition at 50 mu M, IC50 = 25.3 mu M) was initially identified as a potent inhibitor of IL-5. This shows the compatible activity with budesonide or sophoricoside. To identify structural requirements, 26 chalcones were prepared and their inhibitory activities were tested against IL-5. Among them, compound 4-[(E)-3-(2-cyclohexylmethoxy-6-hydroxyphenyl)-3-oxoprop-1-enyl]benzenesulfonamide (2w, 99.5% inhibition at 50 mu M, IC50 = 1-8 mu M) shows the most potent activity. The important structural requirements of these chalcone analogs exhibiting the inhibitory activity against IL-5 were recognized as the following. (1) The hydrophobic group such as benzyloxy or cyclohexylmethoxy at 6-position of A ring is necessary. (2) The existence of phenolic hydroxyl at 6-position of A ring is critical. (3) Propenone unit as alpha,beta-unsaturated ketone is essential. (4) Electron withdrawing groups with hydrogen acceptor property at 4-position of B ring enhance the activity and quantitative structure-activity relationship of 2 regarding these substituents was determined. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: AIRWAY HYPERRESPONSIVENESS; SOPHORICOSIDE ANALOGS; MOLECULAR-CLONING; IL-5; EOSINOPHILIA; EXPRESSION; HYPERREACTIVITY; RECEPTORS; BINDING; LEADS